A novel symmetric cryptographic method to design block complexity for data security. (December 2022) - Umapathy, B.; Kalpana, G.
Highlights: Introducing the new multi-layered cryptographic algorithm named as UK to secure the Cloud Storage data. The motive of novel cryptographic algorithm is to create a complex transformation method for plain text to cipher text, with high complexity in average encryption and decryption time. Create multi-layered security system by employing multiple passwords which is given directly by the user. It should be compatible for image, video, audio, document and text. Abstract: The growth and development of Cloud Computing from its inception till today has made a tremendous progress and the evident of the same is seen in every walk of life. However considering data security there is a big hiatus. It is consistently under threat besides many guards. This in turn has created a research gap to find out the secure guard for Data Security. Data security is primarily dependent on encryption algorithms to secure data in the CC environment. Thus the encryption algorithm plays a predominant role in Cloud Storage (CS) which is a place to store all the data of the users or data owners. Hence the usage of CS has become inevitable in almost all fields including education, industry, business and the usage of the same is grown in leaps and bounds particularly in the pandemic. The metamorphosis of the encryption algorithm (i.e. AES, Triple DES, and Blowfish) has a complex formation to secure the data. However complex the formation is; it fails to cope with the modern-day processer evaluation. The complexity level tends to be low considering the performance of the modern-day processer evaluation. Hence an alternate solution is demanded and this research paper has attempted to meet the demand by introducing the new multi-layered cryptographic algorithm named as UK to secure the CS data. This UK algorithm follows an entirely new transformation procedure to secure the data. It creates huge complexity in reasonable encryption time, even though brute force needs to be more complex ever. The key and Metadata are not stored in any place so that the CS service provider will not be able to do anything in this structure. In this case, the database service providers have the hold of the encrypted data of the user which cannot be accessed by any attacking techniques. Hence, the CS provider becomes the warehouse maintainer. Graphical abstract: Image, graphical abstract